2016
DOI: 10.3748/wjg.v22.i40.8978
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the quality of life of patients after gastrectomy as assessed using the newly developed PGSAS-45 scale: A nationwide multi-institutional study

Abstract: AIMTo identify certain clinical factors other than the type of gastrectomy which affect the postoperative quality of life (QOL) of patients after gastrectomy.METHODSThe postgastrectomy syndrome assessment scale (PGSAS)-45 was designed to assess the severity of symptoms, the living status and the QOL of gastrectomized patients. It consists of 45 items, of which 22 are original items while 23 were retrieved from the SF-8 and Gastrointestinal Symptoms Rating Scale questionnaires with permission. A nationwide surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Accordingly, several studies have used the PGSAS-45 to assess QoL after laparoscopic gastrectomy. Notably, the QoL of patients after laparoscopic gastrectomy after 1 year is similar to that of patients after open standard gastrectomy (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Accordingly, several studies have used the PGSAS-45 to assess QoL after laparoscopic gastrectomy. Notably, the QoL of patients after laparoscopic gastrectomy after 1 year is similar to that of patients after open standard gastrectomy (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 78%
“…The advantage of local resection is that it minimizes functional impairment. Local resection was shown by the PGSAS studies to be more superior to standard gastrectomy in terms of almost all subscales of the PGSAS (5,6).…”
Section: Requirements Of the Laparoscopic Local Resection Of Stomachmentioning
confidence: 95%
“…Although many postgastrectomy symptoms are subjective and scientific approaches to quantify them have been difficult, a specific questionnaire, the postgastrectomy syndrome assessment scale-45 (PGSAS-45), was developed as a psychometric measurement of PGS. PGSAS-45 measures outcomes from the patient's point of view, and nearly 2,400 questionnaires were collected during the PGS assessment study (PGSAS study), thus providing essential data to verify PGS scientifically (4)(5)(6)(7). The subjects of the PGSAS study were stage IA or IB cases at least one year after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Roux‐en‐Y esophagojejunostomy (RY) with D2 lymph node resection for advanced gastric cancer has been widely employed as a standard reconstruction after total gastrectomy (TG) in Japan . However, RY is often associated with postoperative disorders, especially a decrease or loss of appetite, alkaline reflux esophagitis (ARE), early dumping syndrome (EDS) and microgastria (decreased food intake), because of defects of the lower oesophageal sphincter (LES), pyloric sphincter and food reservoir functions after TG . Therefore, it is important for surgeons to prevent ARE, EDS and microgastria, which can markedly impair the quality of life (QOL) and nutritional status of patients after TG.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, RY is often associated with postoperative disorders, especially a decrease or loss of appetite, alkaline reflux esophagitis (ARE), early dumping syndrome (EDS) and microgastria (decreased food intake), because of defects of the lower oesophageal sphincter (LES), pyloric sphincter and food reservoir functions after TG. [1][2][3][4][5] Therefore, it is important for surgeons to prevent ARE, EDS and microgastria, which can markedly impair the quality of life (QOL) and nutritional status of patients after TG. We previously reported that RY after TG, preserving the LES, can restore physiological conditions, and thus prevent ARE in patients.…”
Section: Introductionmentioning
confidence: 99%